2019
DOI: 10.1101/739557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supporting evidence for DNA shearing as a mechanism for origin unwinding in eukaryotes

Abstract: Our earlier study demonstrated that head-to-head CMGs that encircle duplex DNA and track inward at origins melt double-strand (ds) DNA while encircling the duplex by pulling on opposite strands and shearing DNA apart (Langston and O'Donnell (2019) eLife 9, e46515). We show here that increasing the methylphosphonate neutral DNA from 10 nucleotides in the previous report, to 20 nucleotides, reveals that CMG encircling duplex DNA only interacts with the tracking strand compared to the non-tracking strand. This si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…4 ). This result strongly supports the idea that T-Ag interacts with the negatively charged phosphate backbone of the tracking strand during duplex DNA translocation, similar to what was observed for CMG tracking on dsDNA ( 40 , 57 ). Somewhat surprisingly, the presence of MePs on the nontracking strand increased unwinding twofold compared with the substrate with no MePs ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4 ). This result strongly supports the idea that T-Ag interacts with the negatively charged phosphate backbone of the tracking strand during duplex DNA translocation, similar to what was observed for CMG tracking on dsDNA ( 40 , 57 ). Somewhat surprisingly, the presence of MePs on the nontracking strand increased unwinding twofold compared with the substrate with no MePs ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…We have also demonstrated that the head-to-head orientation of the two CMGs enables them to rip, or shear, the duplex apart, similar to the model of Fig. 6 B and proposed here for T-Ag ( 40 , 57 ).…”
Section: Discussionsupporting
confidence: 81%
“…This conundrum has recently been solved. Briefly, the two CMGs push inward toward one another by pulling on opposite strands of the duplex, and this generates sufficient torque to separate the duplex into single-strands [ 62 , 63 ]. The CMGs then use a ssDNA gate within the Mcm2–7 ring to expel the lagging strand, as demonstrated in recent single-molecule studies [ 64 ], and in biochemical ensemble studies [ 23 ].…”
Section: Cmg Tracks On Dna N-tier First At a Replication Forkmentioning
confidence: 99%